Алтын ордада ислам: таралуы мен Еуразия даласына әсері - Abylov, T. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
In this paper the Islamization process of the Golden Horde and its results will be discussed. The Golden Horde has unified the areas such as Desht-i Kipchak, Crimea, Volga Bulgaria and the North Caucasus, which were very different from each other in cultural, religious and political aspects. As a result, inter-religious and international cultural change has increased and a unique syncretic Golden Horde culture has emerged. In the Golden Horde, a religious tolerance policy was carried out where Muslims, Christians, Buddhists, Jews and many other religious groups lived peacefully. This was a very rare case for the Middle Ages time. After a while when Islam strengthened, it became an official religion of the state in the Golden Horde. This case leads us to study the political and cultural context of religious change. The aim of the article is to look into the stages of the Islamization of the Golden Horde starting from the upper class of the its society to ordinary people. Also to find out how the Golden Horde became the center of the Islamic world in the Northern Eurasian steppes. Key words: Golden Horde, Turko-Mongol state, Kipchaks, religion, Islam, Desht-i Kipchak, sufism.